Anaemia in elective orthopaedic surgery – Royal Adelaide Hospital, Australia. Issue 1 (27th January 2016) - Kearney, B.; To, J.; Southam, K.; Howie, D.; To, B.
Abstract: Background: An anaemia clinic was established to improve the preoperative management of elective orthopaedic patients scheduled for arthroplasty. This paper is a report on the first 100 patients assessed. Aim: To assess the incidence and causes of anaemia in patients on a waiting list for elective arthroplasty in a public hospital and to assess the impact of anaemia detection in this patient population. Methods: Patients attending an Anaemia Clinic for elective orthopaedic surgical patients, during March 2010 to June 2013 were studied. Outcome measures included change in haemoglobin preoperative results and perioperative transfusion rates by preoperative haemoglobin. Results: Seventeen per cent of patients scheduled for elective surgery were found to be anaemic. Of the 100 patients who attended, approximately half were found to be iron deficient and the remainder had anaemia of chronic disease. Serum ferritin <30 µg/L alone did not identify iron deficiency in 80% of patients with iron deficiency. Patients with iron deficient anaemia were able to be treated, in all cases, to achieve a significant increase in preoperative haemoglobin. The general unavailability of erythropoietin limited effective intervention for the non‐iron‐deficient anaemic patients. Seven patients had their surgery cancelled because of the screening programme. Conclusions: Half of the anaemic patients in a joint replacement screening clinic were iron deficient, and treatment was effective in improving the pre‐operative haemoglobin and reducing perioperative transfusion rates. This screening process should improve patient outcome. Another important finding in this group of patients is that ferritin levels cannot be reliably used as the sole indicator in the diagnosis of iron deficiency anaemia in this group of patients undergoing elective arthroplasty.